2020
DOI: 10.1007/s12011-020-02074-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum Selenium, Iron, Zinc, and Copper Concentrations in Renal Transplant Recipients Treated with Mycophenolate Mofetil

Abstract: There are data available in the literature on bioelement concentrations in the serum of various groups of patients; however, very little is known about the serum concentration of selenium (Se), iron (Fe), zinc (Zn), and copper (Cu) in renal transplant patients treated with immunosuppressive drugs, including mycophenolate mofetil (MMF). Monitoring of serum bioelement concentrations in renal transplant recipients is of profound importance, as the proper bioelement levels seem to prolong the normal function of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Low levels of selenium are found in some regions of the world [70,71]. In our country, the average Se concentration is 70 µg/L (50−55 µg/L in some regions), and in North America it is 122.4−151.8 µg/L [70,73,74]. Recommendations for the optimal amount of Se in the diet are based on maximizing glutathione peroxidase (GPx) [70,71].…”
Section: Discussionmentioning
confidence: 93%
“…Low levels of selenium are found in some regions of the world [70,71]. In our country, the average Se concentration is 70 µg/L (50−55 µg/L in some regions), and in North America it is 122.4−151.8 µg/L [70,73,74]. Recommendations for the optimal amount of Se in the diet are based on maximizing glutathione peroxidase (GPx) [70,71].…”
Section: Discussionmentioning
confidence: 93%
“…It is possible that disturbances in glucose homeostasis during progressing inflammatory processes are related to higher levels of urinary Cr loss. Some authors have observed that hyperglycemia is a poor prognostic factor in severe infections such as malaria and COVID-19 [ 61 ]. Similarly, Zeng et al [ 28 ] found that disturbances in urinary concentrations of Cr and Mn are associated with severe illness, which was also observed in mice during Acanthamoeba sp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that immunosuppressive drugs, which increase the concentration of Cu and Zn in the blood serum, also reduce the concentration of Na [ 64 ]. Wilk et al [ 61 ] found higher levels of Fe in patients treated with immunosuppressive drugs, including mycophenolate mofetil (MMF).…”
Section: Discussionmentioning
confidence: 99%
“…2, Pomeranian Medical University, in Szczecin in northwestern Poland. The experiment is the continuation of our previous experiment [25,26]. Patients were characterized by stable function of renal graft for over six months.…”
Section: Study Populationmentioning
confidence: 99%
“…The blood mercury concentration can rise to 35 μg/L after long-term exposure to mercury vapor [ 22 ]. Renal transplant recipients need to use immunosuppressive drugs (IDs) in order to avoid graft rejection, but these IDs affect magnesium (Mg), sodium (Na), [ 23 ], and iron (Fe) status in blood [ 24 ], as well as that of selenium (Se), copper (Cu), zinc (Zn), and Fe [ 25 ]. Our previous data have indicated that mycophenolate mofetil alters the concentration of arsenic and selenium concentration in blood of renal transplant recipients [ 26 ].…”
Section: Introductionmentioning
confidence: 99%